2018
DOI: 10.1007/s00784-018-2540-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of root canal sealers on the fracture resistance of endodontically treated teeth: a systematic review of in vitro studies

Abstract: A considerable heterogeneity was found in the methodologies of included studies. Therefore, this review strongly suggests the development of standardized methods to test the reinforcement effect of root canal filling materials in in vitro studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 66 publications
0
27
2
Order By: Relevance
“…A complete root canal filling is substantial for long-term success of endodontic treatment 1 . The obturation is classically performed using gutta-percha and different types of root canal sealers 2 . The root canal sealers fill the gaps between gutta-percha cones and the dentine walls 3 .…”
Section: Introductionmentioning
confidence: 99%
“…A complete root canal filling is substantial for long-term success of endodontic treatment 1 . The obturation is classically performed using gutta-percha and different types of root canal sealers 2 . The root canal sealers fill the gaps between gutta-percha cones and the dentine walls 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Vertical root fracture (VRF) is a serious complication that can occur in up to 20% endodontically treated teeth that eventually ends with tooth extraction 4 . For measurement of fracture resistance of specimens, Instron testing machine was used.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of sealers on fracture resistance of endodontically treated teeth is debatable. A critical review by Kim et al (3) concluded that adhesive procedures of methacrylate resin based sealers were not able to strengthen dentin after root canal treatment, while a systematic review done by Uzunoglu-Özyürek (4) concluded that root canal sealers increased fracture resistance of endodontically treated teeth. The purpose of this study was to compare fracture resistance of roots after obturation with gutta-percha and Endofil, Adseal, and MTA-Fillapex sealers.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the comparisons among the sealers, no conclusions could be drawn for the superiority of one sealer type to another’ (Uzunoglu‐Özyürek et al . ). Example 9b : ‘This systematic review, which was based on one low powered small sample trial assessed as at low risk of bias, illustrates that there is insufficient evidence to determine whether antibiotics reduce pain or not compared to not having antibiotics. The results of this review confirm the necessity for further larger sample and methodologically sound trials that can provide additional evidence as to whether antibiotics, prescribed in the preoperative phase, can affect treatment outcomes for irreversible pulpitis’ (Agnihotry et al .…”
Section: Explanation and Endodontic Examples Of Items In The Prisma Fmentioning
confidence: 97%
“…Regarding the comparisons among the sealers, no conclusions could be drawn for the superiority of one sealer type to another’ (Uzunoglu‐Özyürek et al . ).…”
Section: Explanation and Endodontic Examples Of Items In The Prisma Fmentioning
confidence: 97%